Contralateral breast lesions detected by breast MRI study - An analysis of 735 Taiwanese women with primary operable breast cancer - Hung-Wen Lai; Wan-Yu Hung; Chih-Wei Lee; Hwa-Koon Wu; Shou-Tung Chen; Dar-Ren Chen; Chih-Jung Chen; Shou-Jen Kuo (Formosan Journal of Surgery, 2017)
Purpose: Women with unilateral breast cancer are at an increased risk for the development of contralateral breast cancers. In this study, we evaluated the incidence and pathology of contralateral breast cancer detection by preoperative magnetic resonance imaging (MRI) in Taiwanese women with primary operable breast cancer. Methods: A retrospective review of patients who received preoperative breast MRI and underwent operation for breast cancer at single institution between January 2011 and December 2013 was conducted. The incidence, pathology, and management methods of MRI-detected contralateral breast lesions were reported and analyzed. Results: A total of 735 patients enrolled in the current study, and 70 patients (9.5%) were found to have contralateral breast lesions detected by preoperative MRI. Among these 70 patients, 44 (62.9%) received surgical intervention for the MRI-detected contralateral occult lesions. Malignancy was detected in the final pathologic specimen in 21 (47.7%) patients, and benign lesions found in 23 (52.3%) patients. Among these 21 MRI-detected occult contralateral breast cancers, there were 7 (33.3%) invasive ductal carcinoma, 1 (4.8%) mucinous carcinoma, and 13 (61.9%) ductal carcinoma in situ. Compared with the pathology of the 735 primary operable breast cancers, MRI-detected contralateral breast cancer was associated with higher in situ carcinoma (61.9% vs. 15.9%, P < 0.01). The positive predictive value of MRI was 37.7%, eight of 28 MRI Breast Image Reporting and Data System(BI RADS)-4 cases had a pathological malignancy; nine of 17 MRI BI RADS-5 cases had a pathological malignancy. Conclusion: In women with known unilateral breast cancer, 2.9% of patients were diagnosed to have synchronous contralateral breast cancer when combined with preoperative breast MRI evaluation. Adequate biopsy or surgical strategy should be discussed in patients whose preoperative breast MRI showed contralateral occult lesions with suspicious for malignancy.